Literasi Digital Bagi Perempuan Penyandang Disabilitas di Kota Makassar - Furqan, Rahmatul; Warandhi, Sartika; Bustamin, Anugrayani (Jurusan Teknik Informatika dan Komputer, 2023)
This training involved the Indonesian Association of Women with Disabilities (HWDI) Makassar as a partner. Women with disabilities have been a marginalized group and have often been discriminated against. Advances in technology actually provide opportunities to increase the participation of women with disabilities as citizens whose rights and obligations are guaranteed by law. However, mastery of technology and digital literacy which is still low actually reinforces the discrimination experienced by them and even presents various challenges and threats. Not a few women with disabilities who become victims of cybercrimes. This problem is also being experienced by most members of HWDI Makassar as partners. For this reason, this community service activity-initiated training of trainers (TOT), alias training for facilitators regarding basic digital literacy for persons with disabilities. The main objective of this activity is to build the capacity of individual HWDI Makassar members with low socioeconomic backgrounds who have been marginalized digitally. Training activities will be carried out for two days with materials related to basic digital device recognition, use of accessibility features, prevention of fake news and crime in online media. There are three main approaches to the training method, namely, the lecture/question-and-answer method, tutorials, and demonstrations. In general, the results of digital literacy training for women with disabilities in Makassar City have increased the knowledge, skills and motivation of women with disabilities in Makassar City. This is reflected in indicators of conformity between planning and implementation, attendance of participants, and results of interviews with participants.